Endovascular Recanalization of Non-acute Symptomatic Middle Cerebral Artery Total Occlusion and Its Short-Term Outcomes - Zheng, Meimei; Song, Yun; Zhang, Jinping; Zhao, Wei; Sun, Lili; Yin, Hao; Zhang, Jun; Wang, Wei; Han, Ju (Frontiers in Neurology, 2019)
Background and Purpose: The optimal treatment for patients with non-acute symptomatic middle cerebral artery (MCA) total occlusion and a high risk of recurrent ischemic stroke despite medical management is not well-established. We aimed to assess the feasibility, safety, and short-term outcomes of angioplasty and stenting for these patients. Methods: Data of 22 patients with non-acute symptomatic MCA total occlusion who have failed medical management and undergone endovascular recanalization were retrospectively collected in our prospective database. All occlusive lesions were predilated with conventional balloons, followed by paclitaxel-coated coronary balloon inflation or not, and then a remedial stenting was performed or not, depending on the discretion of the operator. The rate of successful recanalization, perioperative outcomes, and short-term outcomes, such as restenosis and stroke recurrence, was analyzed. Results: Successful recanalization was achieved in 95.5% of patients, with 14 patients undergoing balloon angioplasty and 7 patients undergoing remedial stenting. Seven patients developed perioperative complications, including one patient with persistent neurological deficit. Over a median clinical follow-up duration of 5.0 months, only one patient had recurrent ischemic symptoms attributed to the cessation of antiplatelet treatment owing to postoperative intracranial hemorrhage. The proportion of patients who achieved favorable clinical outcome (modified ranking scale score of 0–2) was 85.7%. Post-procedural repeat vascular imaging was performed at 4.5 ± 1.84 months, with nine and one patient undergoing cerebral angiography and magnetic resonance angiography, respectively. One (10%) artery presented with asymptomatic reocclusion. Conclusions: Angioplasty and stenting may be feasible for the patients with non-acute symptomatic atherosclerotic MCA total occlusive disease who have failed medical management.